FTIR spectroscopic evaluation of sucrose-maltodextrin-sodium citrate bioglass - Sritham, Eakasit; Gunasekaran, Sundaram (My University, 2017)
A model bioglass system was composed with sucrose (SC), maltodextrin (MD), and sodium citrate (NaCit). Samples were prepared with different SC/MD ratios (7:3, 5:5 and 3:7, by mass) and NaCit/SC ratios (0, 0.1 and 0.2, by mole) at low (0.27–0.49 %wb) and high (2.83–4.4 %wb) levels of moisture content. The effects of system constituents were investigated using the Fourier transform infrared (FTIR) spectroscopy. Hydrogen bonding interactions analyzed by studying the OH-stretching absorption band in the FTIR spectra indicated that there was no noticeable effect of moisture on the bioglass. The matrix of the system with high concentration of MD was loosely packed. NaCit interacted with both SC and MD through carboxylic groups, as evidenced by the shifting of antisymmetric (νas(COO−)) and symmetric (νs(COO−)) stretching bands of carboxyl groups. However, NaCit tended to interact more strongly with SC rather than with MD as evidenced by the strongest hydrogen-bonded network observed in the system with highest concentrations of SC (i.e., SC/MD = 7:3) and NaCit (i.e., NaCit/SC = 0.2).
Keywords: Bioglass; Glycosidc linkage; OH-Stretching vibrations; Spectroscopy